The Correlation of ?/? mRNA Ratio with Clinical and Hematological Parameters in Patients with ?-thalassemia Syndrome (Iraqi Journal of Medical Sciences, 2022)
Background: Thalassemias are a group of genetically transmitted blood diseases characterized by defects in the production of ?- or ?-chains of hemoglobin called ?-thalassemia and ?-thalassemia, respectively. One of the common features of ?-thalassemia is ineffective erythropoiesis because of the imbalance of globin chain production, which result in increased apoptosis during erythroblast maturation. Objective: To evaluate the ß/? globin mRNA ratio in patients with ß-thalassemia syndrome and to correlate the ß/? ratio with hematological and clinical condition of the patients.Methods: Thirty-five patient samples were collected from Thalassemia Centre of Ibn Al-Balady Hospital; 18 patients with ?-thalassemia major and 17 patients with ?-thalassemia intermedia. The patients were randomly selected regarding sex, whereas their age ranged from 3 to 17 years. Along with those samples, twenty control leftover samples that were the remaining of samples collected for laboratory investigation, were taken from Al-Kadhimiya Pediatric Hospital, and were age and sex matched with the patients group. The ? and ? globin chain ration were calculated by the real-time reverse transcription-polymerase chain reaction (qRT-PCR). The ?/? -globin mRNA ratio of the samples was measured by the 2???CT method. Results: Analysis of the ?-globin/?-globin mRNA ratio showed that disease severity increased with a reduction of the ratio. There was a highly significant difference in ? level, ß level and ß/? ratio among studied groups with a p value of (p < 0.001). The highest level was in control group, followed by that in ?-thalassemia intermedia and the lowest was in ?-thalassemia major.Conclusion: The severity of ß/? globin chain imbalance showed a significant and negative correlation with the mean corpuscular volume and there was no significant correlation between the ß/? ratio and markers of erythropoiesis in ß-thalassemia major and ß-thalassemia intermedia patients. The ß/? ratio was a good tool for diagnosis in ß-thalassemia major and ß-thalassemia intermedia as compared to control group with high sensitivity and specificity. A ß-chain gene expression was the lowest in ß-thalassemia major followed by ß-thalassemia intermedia as compared to control group.Keywords: Thalassemia, ß/? -globin mRNA ratioCitation: Yousif MH, Al-Mamoori HS. The Correlation of ?/? mRNA Ratio with Clinical and Hematological Parameters in Patients with ?-thalassemia Syndrome. Iraqi JMS. 2022; 20(1): 139-145. doi: 10.22578/IJMS.20.1.18
Keywords: Thalassemia; globin mRNA ratio